The Effect of Compensation and Workload on Turnover Intention Through Job Satisfaction as an Intervening Variable in Security Outsourcing at PT Putratama Satya Bhakti in the Jakarta Area - Melinda Pauziah; Febrisi Dwita (International Journal of Business, Law, and Education, 2026)
This study aims to determine the effect of compensation and workload on turnover intention through job satisfaction as an intervening variable among outsourcing security employees at PT Putratama Satya Bhakti Jakarta Area. The population in this study is all outsourcing security employees at PT Putratama Satya Bhakti Jakarta Area. The sampling technique used is non-probability sampling with the purposive sampling method. The sample size in this study is 93 respondents. The analysis method used is path analysis with the assistance of SPSS version 27. The results of this study indicate that compensation and workload have a positive and significant effect on job satisfaction. Furthermore, compensation does not have a significant effect on turnover intention, while workload has a positive and significant effect on turnover intention. The results of the Sobel Test also indicate that job satisfaction cannot mediate the effect of compensation and workload on turnover intention. The research findings show that turnover intention among outsourced security employees at PT Putratama Satya Bhakti Jakarta Area is more directly influenced by workload rather than through job satisfaction. High job demands and work pressure are factors that drive turnover intention, so companies need to manage workload and create comfortable working conditions to reduce employee turnover intention.